Rwanda : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and the FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
This paper analyzes Rwanda's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, and the Financial Action Task Force Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. Rwanda's economic performance is vulnerable to shocks, in particular a sharp fall in aid flows. The domestic financial sector still faces a poor environment with economic activity concentrated in a few sectors and a weak credit culture. There are serious shortcomings in the accounting and auditing systems and the institutional, legal, and judicial frameworks.